Growth of the upper crust in intra-oceanic island arcs by intrusion of basaltic magmas: the case of the Koloula Igneous Complex, Guadalcanal, Solomon Islands (SW Pacific) - Sotiriou, Paul; Haase, Karsten; Schneider, Kathrin; Grosche, Anna; Nöbel, Kristina; Chivas, Allan R. (Contributions To Mineralogy and Petrology, 2022)
The Pleistocene (2.2–1.5 Ma) Koloula Igneous Complex (KIC) on Guadalcanal in the Solomon island arc consists of a low-K calc-alkaline sequence of ultramafic to felsic plutonic rocks. We present whole-rock major and trace element and Sr–Nd-Pb isotope data, as well as mineral compositions that record the magmatic evolution of the complex. The intrusive sequence is grouped into two cycles, Cycle 1 and 2, comprising gabbroic or dioritic to granodioritic rocks. The major and trace element data of each cycle forms a single calc-alkaline fractional crystallisation trend. The distinct radiogenic isotope and incompatible element compositions of the Cycle 1 and 2 intrusions imply slightly different mantle sources. The KIC formed by shallow (0.1 GPa) fractional crystallisation of mantle-derived Al-rich basaltic parental magmas (6–8 wt.% MgO) that were formed by deeper-level (0.7 GPa) fractionation of olivine and pyroxene from Mg-rich ( 11 wt.% MgO) primary magmas in the Solomon intra-oceanic island arc. Olivine, clinopyroxene, plagioclase, amphibole, biotite, apatite, and Fe–Ti oxides fractionated from the KIC’s high-Al basaltic parental magmas to form calc-alkaline magmas. Liquid line of descent trends calculated using mass balance calculations closely match major element trends observed in the KIC data. The KIC crystallised at shallow, upper crustal depths of 2.0–3.0 km in 20 km-thick island arc crust. This complex is typical of other Cenozoic calc-alkaline ultramafic to felsic plutons in Pacific intra-oceanic island arcs in terms of field relationships, petrology, mineral chemistry and whole-rock geochemistry. Hornblende fractionation played a significant role in the formation of the calc-alkaline felsic plutonic rocks in these Cenozoic arc plutons, causing an enrichment of SiO2 and light rare earth elements. These plutons represent the fossil magma systems of arc volcanoes; thus, the upper arc crust is probably generated by migration of magmatic centres.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Basaltic magmas; Fractional crystallisation; Island arcs; Koloula; Plutonic; Solomon Islands

Petrogenesis of anorthosites throughout Earth history - Sotiriou, Paul; Polat, Ali (Precambrian Research, 2023)
Petrologists are still trying to solve the ‘anorthosite problem’, which was first identified by N.L. Bowen in 1917 and revolves around the uncertainty surrounding the petrogenesis, tectonic setting, emplacement, and parental magma compositions of anorthosites. Anorthosites are volumetrically minor to significant, occur worldwide and have implications for upper mantle depletion, oceanic and continental crust growth and evolution, the longevity of plate tectonic processes on Earth, and magma chamber processes. Anorthosites have formed throughout Earth history from 3950 Ma to the Present. Anorthosites are far more common than previously thought as there are at least 2,126 known preserved anorthosite occurrences worldwide. Anorthosites are closely associated with gabbros and leucogabbros and spatially associated with pillow-bearing mafic volcanic rocks in ophiolites and layered intrusions, except for Proterozoic anorthosites that are closely associated with intermediate to felsic intrusives. Archean anorthosites often contain near-spherical calcic plagioclase (An70-100) megacrysts up to 45 cm in diameter and magmatic amphibole, Proterozoic anorthosites have elongate (≤1 m) andesine (An30-50) megacrysts, and Phanerozoic anorthosites contain calcic plagioclase (An70-100). The plagioclase anorthite contents of anorthosites vary throughout Earth history, troughing in the Proterozoic. This corroborates the whole-rock geochemistry of anorthosites, which also varies throughout Earth history and indicates that crustal contamination played a significant role in the petrogenesis of Proterozoic anorthosites. Relatively high mantle heat flow and partial melting and the thermal blanketing of Proterozoic supercontinents led to the generation of large anorthosite massifs. Archean, Proterozoic and Phanerozoic anorthosites crystallised from tholeiitic or high-Al tholeiitic parental magmas that were derived from depleted mantle sources and significantly assimilated continental crust in the Proterozoic. Archean anorthosites crystallised from hydrous Ca- and Al-rich tholeiitic parental magmas derived by partial melting of hydrated sub-arc depleted mantle sources. Anorthosites have predominantly formed in subduction-related settings throughout Earth history, indicating that plate tectonic processes have operated since the beginning of the Eoarchean. The proportion of subduction-related anorthosites significantly declined in the Proterozoic following supercontinent amalgamation. Calcic megacrystic anorthosites and massif-type anorthosites are largely restricted to the Archean and Proterozoic, respectively, yet they occur throughout Earth history. The petrogenesis of anorthosites reflects the secular evolution of the Earth.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Anorthosites; Archean; Earth history; Phanerozoic; Proterozoic; Secular evolution

Temporal variations in the incompatible trace element systematics of Archean TTGs: Implications for crustal growth and tectonic processes in the early Earth - Sotiriou, Paul; Polat, Ali; Windley, Brian; Kusky, Timothy (Earth-Science Reviews, 2023)
In this study, we applied classification and tectonic setting diagrams, N-MORB-normalised trace element and incompatible element temporal variation diagrams, Nb/Nb*, Pb/Pb*, La/Smn, La/Nbn, Th/Nbn and Pb/Cen ratios and field-structural relationships to Archean tonalites, trondhjemites and granodiorites (TTGs) and Phanerozoic arc-generated TTGs. Geochemical analyses were compiled from the literature to elucidate how Archean continental crust formed, whether plate tectonics operated in the Archean, if this Archean form of plate tectonics resembled modern-style plate tectonics, and when plate tectonics commenced in the early Earth. The Archean TTGs used for this study were not noticeably influenced by alteration or crustal contamination; therefore, their geochemistry is indicative of their original juvenile sources and the tectonic environments in which they were generated. These rocks are predominantly calcic to calc-alkalic and magnesian granitoids derived from low-K mafic/tholeiitic sources. Most Archean TTGs have high La/Ybcn and Sr/Y ratios and low Ybcn values and Y contents characteristic of adakites and formed by partial melting of subducting oceanic crust or the lower arc crust. However, some Archean TTGs resemble modern arc andesites, dacites and rhyolites that have low La/Ybcn and Sr/Y ratios and high Ybcn values and Y contents and formed by fractional crystallisation of basaltic magmas derived from partial melting of the sub-arc mantle wedge. Archean TTGs overlap with their Phanerozoic counterparts and mainly plot in the arc fields of tectonic setting discrimination diagrams. The N-MORB-normalised trace element patterns of Archean TTGs from well-studied cratons bear a striking resemblance to those of TTGs from modern active arcs (e.g., Izu-Bonin-Mariana, Andean) and from older Phanerozoic arcs (e.g., Sierra Nevada, Gangdese), consistent with their formation in arcs. The temporal variations in the trace element geochemistry of Archean TTGs underwent a noticeable change on a global scale at ca. 3500–3200 Ma. The vast majority (99%) of Archean TTGs have Nb/Nb* and Pb/Pb* anomaly ratios of <1 and >1, respectively, and are interpreted to have formed in arc settings; the remainder had non-arc origins. The La/Smn, La/Nbn, Th/Nbn and Pb/Cen ratios of these TTGs suggest that 99% of these rocks formed in supra-subduction zone settings, namely arcs, forearcs and back-arcs, the remainder being derived from mantle plumes and mid-ocean ridges. This study suggests that throughout the Archean TTGs were generated in subduction zones by modern-style plate tectonic processes, beginning in the Hadean (>4000 Ma). TTGs began to form in intra-oceanic arcs at ca. 4020 Ma prior to a global-scale switch to Andean-style continental arc magmatism at ca. 3500–3200 Ma, which led to the genesis of TTGs in continental arcs worldwide in the Paleoarchean. Modern-style plate tectonic processes predominantly contributed to the formation of Archean continental crust. As such, global-scale vertical tectonic processes did not play a significant role in the formation of Archean continental crust. Most plutons are emplaced vertically into the crust, as exemplified by modern arcs. Vertical tectonic processes are locally observed in Archean cratons, leading many researchers to erroneously conclude that vertical tectonic processes were predominant in the early Earth.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Archean tectonics; Early Earth processes; Incompatible trace element systematics; TTG petrogenesis; TTGs

Temporal variations in the incompatible trace element systematics of Archean volcanic rocks: Implications for tectonic processes in the early Earth - Sotiriou, Paul; Polat, Ali; Windley, Brian F.; Kusky, Timothy (Precambrian Research, 2022)
Temporal variations in the incompatible trace element geochemistry of volcanic rocks in Archean greenstone belts have major implications for the style of tectonics that operated in the early Earth, and if and when plate tectonic processes occurred in the Archean, which are still subjects of substantial debate. Comparing the geochemistry of Archean volcanic rocks with that of Phanerozoic arc volcanic rocks has the potential to shed light on these questions. Geochemical data from 8,249 Eoarchean to Neoarchean volcanic rocks and 20,099 Phanerozoic arc volcanic rocks were compiled from the literature to address the above questions through the application of temporal incompatible trace element ratio variations, N-MORB-normalised trace element diagrams, and tectonic setting discrimination diagrams. The sampled rocks range in composition from ultramafic through basaltic and andesitic to dacitic/rhyolitic. Most of the incorporated Archean volcanic rocks were deemed to have been unaffected by significant alteration or crustal contamination in the literature and, therefore, to reflect their provenance, a feature that was corroborated by this study. Most of these Archean volcanic rocks plot in the plate margin, oceanic arc and continental arc fields in classification and tectonic setting discrimination diagrams, with the remainder plotting in the alkaline arc, mid-ocean ridge and oceanic island fields. Comparison between N-MORB-normalised trace element diagrams of volcanic rocks from well-studied Archean greenstone belts in Greenland, Canada, South Africa, China, Australia, India, Brazil and Finland and volcanic rocks from well-studied modern arcs demonstrates that their trace element patterns are remarkably similar. This indicates that the former formed in arc-related settings by modern-style plate tectonic processes that operated throughout the Archean. The Pb and Nb anomalies of most Archean volcanic rocks are fully consistent with an arc-related setting. The temporal variations in the incompatible trace element ratios of Archean volcanic rocks, coupled with their lithological associations, demonstrate that intra-oceanic arc magmatism was prominent in the Eoarchean before a shift in these ratios in the Paleoarchean signified the beginning of Andean-style continental arc magmatism between 3500 and 3200 Ma. Modern-style plate tectonic processes were a far more important contributor to Archean crustal growth and evolution than sagduction-driven vertical tectonic processes.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Archean tectonics; Archean volcanic rocks; Modern arc volcanic rocks; Temporal variation; Trace element systematics

The Geoheritage of Madeira: Implications for Natural Heritage and Geotourism - Sotiriou, Paul; Nunes, Pedro (Geoheritage, 2024)
The island of Madeira forms part of the Madeira Archipelago, an Autonomous Region of Portugal, in the NE Atlantic Ocean. The Madeira Archipelago was built on 140-million-year-old oceanic crust. The exposed geology of Madeira is comprised of the Miocene (> 5.6 million years old) Basal (Inferior), Pleistocene-Miocene (1.8–5.6 million years old) Intermediate Volcanic, Pleistocene (0.7–1.8 million years old) Upper (Superior) Volcanic, and Holocene-Pleistocene (0.007-0.7 million years old) Upper (Superior) Volcanic complexes, generating the landforms and landscapes for which the island is renowned. There are at least 17 geosites on Madeira, including those in the Ponta de São Lourenço, Porto da Cruz, São Vicente Valley, Pico Ruivo, and Ponta da Cruz areas. Geotourism is not as well developed as cultural or biodiversity tourism on Madeira, however, it represents another way for tourists to explore the island’s natural heritage if done in a sustainable manner. Future studies are required to better delineate and set up georoutes on Madeira, particularly in the Ponta de São Lourenço, Porto da Cruz, and São Vicente Valley areas. It is envisaged that the aforementioned geosites could be linked by a single georoute around Madeira, the Madeira Georoute. Further investigation of the geosites identified by this study is required to ensure that these sites are managed and conserved, thereby protecting the geoheritage of Madeira. Geoconservation, sustainable tourism and the cooperation between the public and government authorities (including geologists) are required to improve geotourism on Madeira. The application of the Inventario Español de Lugares de Interés Geológico (IELIG) and Geosite Assessment (GA) models are required to assess and manage threats to Madeira’s geoheritage sites. Such threats include coastal erosion and human activities, such as mass tourism and urban expansion. It is proposed that the government of the Autonomous Region of Madeira in consultation with local and regional stakeholders should submit an application to create a UNESCO Global Geopark on the island of Madeira. This territorial sustainable development approach should be implemented based on the principles of geotourism, geoconservation, and geoeducation.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Geoconservation; Geoheritage; Geotourism; Madeira; Natural heritage

Volcanic Landscapes and Geotourism Development: Analysing How Madeira’s Volcanic Origin Shapes its Tourism Industry, with a Focus on Hiking Tours and Scenic Viewpoints - Sotiriou, Paul; Nunes, Pedro (Geoheritage, 2025)
The volcanic landscapes of Madeira, part of the Madeira Archipelago in the NE Atlantic Ocean, form arguably the defining features of the island. The volcanic landscapes occur in the geoheritage sites of Madeira compiled by Sotiriou and Nunes (2024), and include those in the scenic viewpoints in the Ponta de São Lourenço, Porto da Cruz, São Vicente Valley, Pico Ruivo, and Ponta da Cruz areas. These volcanic landscapes contain geological features of interest, such as lava flows, columnar jointing, dykes, tuffs, and volcanic cones. These volcanic landscapes form the natural scenery for which Madeira is renowned. Geotourism is not as well developed as cultural or biodiversity tourism in Madeira, however, the island’s scenic viewpoints of volcanic landscapes have shaped its tourism industry and provide the potential for the development of hiking tours. Therefore, Madeira’s volcanic origin has greatly shaped the tourism industry on the island and has the potential to continue to do so in the future. Geotourism in Madeira could increase in the future due to the creation of hiking tours of the island’s scenic viewpoints of its volcanic landscapes. The creation of the Madeira Georoute and a UNESCO Global Geopark in Madeira could enhance hiking tours and geotourism, especially if done in a sustainable manner. Hiking tours of the scenic viewpoints of volcanic landscapes in the Ponta de São Lourenço, Porto da Cruz, São Vicente Valley, Pico Ruivo and Ponta da Cruz areas could be set up easily using existing tourism infrastructure, such as roads, parking, accommodation, and restaurants. The existence of hiking trails in Madeira’s geosites provides a good foundation for the development of the proposed Madeira Georoute and UNESCO Global Geopark in Madeira.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Geotourism; Hiking Tours; Madeira; Scenic Viewpoints; Tourism Development; Volcanic Landscapes